2023
DOI: 10.1097/prs.0000000000010315
|View full text |Cite
|
Sign up to set email alerts
|

’Implant-based and DIEP flap breast reconstruction: a comparison of breast sensation and quality of life within a singular patient sample’’

Abstract: Background: In this cohort study, the authors compared breast sensation and quality of life (QoL) after replacement of an implant-based breast reconstruction with a deep inferior epigastric perforator (DIEP) flap reconstruction in a singular sample of women. Methods: Women with implant-based breast reconstruction before their DIEP flap were included. Women formed their own control. Breast sensation was measured using Semmes-Weinstein monofilaments. QoL was evaluated using BREAST-Q questionnaires. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…[14,16] Van Rooij et al recently showed that swapping an implant reconstruction for a DIEP ap initially decreases postoperative sensation, but that sensation levels return to their preoperative value after approximately 1.5 years. [17] However, whether an implant does or does not in uence postoperative sensation of the DIEP ap had not been studied before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14,16] Van Rooij et al recently showed that swapping an implant reconstruction for a DIEP ap initially decreases postoperative sensation, but that sensation levels return to their preoperative value after approximately 1.5 years. [17] However, whether an implant does or does not in uence postoperative sensation of the DIEP ap had not been studied before.…”
Section: Discussionmentioning
confidence: 99%
“…have found no correlation between implant volume and breast sensation when the implant is in place. [17] Second, the data used in our study has been collected prospectively for another study but has been retrospectively analyzed for the current study. Hence, we have included as much patients as possible but have not performed a power analysis speci cally for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the TE may have served as a barrier, partially preventing nerve growth toward the skin coming from underneath the pectoralis major muscle 8 . Also, the replacement of the TE with the DIEP flap causes renewed damage to the growing nerve sprouts and significantly influences postoperative breast sensation, since it is an additional surgery 4 …”
mentioning
confidence: 99%
“…In this issue of Plastic and Reconstructive Surgery , van Rooij et al present a cohort study comparing breast sensation and quality-of-life measurements in patients undergoing replacement of implant-based breast reconstruction with deep inferior epigastric perforator (DIEP) flaps with and without neurotization. 1 The authors’ stated aim was to be able to better inform women about what to expect should they decide to undergo implant removal and breast reconstruction with a DIEP flap.…”
mentioning
confidence: 99%